Values and the personality of citizen in the context of the development of the ideas of the «Frankfurt School» - Seropian R. I. (Socio-Pedagogical Issues of Education and Upbringing, 2022)
the history of the last decades of the twentieth century shows that we live in a world where citizenship, social significance and self-awareness not only fundamental for the individual, but preserving the independence, social stability and security of the state. A person who claims to be a citizen is distinguished by patriotism, a desire to demonstrate civic courage and dignity and the ability and willingness to defend his or her country. The following article examines the representatives of the «Frankfurt School» who made an invaluable contribution to the creation of the theory and practice of civic and patriotic education.
Keywords: педагогика; образование; культура; патриотизм; государство; гражданственность; ценности; education; the state; методология; values; Patriotism; methodology; culture; гражданин; pedagogy; citizenship; воспитание личности; citizen; personal education